(untitled) (Research, Society and Development, 2019)
The purpose of this article is to discuss the effectiveness of article 8, section IX of the Maria da Penha Law, which emphasizes "the emphasis in curriculum at all levels of education on contents related to human rights, gender equity and of race or ethnicity, and to the problem of domestic and family violence against women.”(Brazil, 2006) This approach was based on bibliographical research, expressing great relevance due to the increasing cases of gender violence throughout the country ratifying the need to rethink solutions to the problem presented. Faced with these issues, it is concluded that despite all social and legal developments regarding the creation of mechanisms to curb gender violence, the gaps that prevent greater effectiveness in the application of article 8, section IX of the Maria da Penha Law in schools, requiring more precise actions on the part of the public power.